Review of Switched Reluctance Motor Control for Acoustic Noise and Vibration Reduction - Furqani, Jihad; Purwadi, Agus (http://dx.doi.org/10.31427/IJSTT.2018.1.2.4, 2018)
Switched Reluctance Motor (SRM) is one of the candidates for substituting permanent magnet motor in Hybrid Electric Vehicle (HEV) application. Compared to permanent magnet motor, SRM is relatively low cost, robust, high reliability, and possible for high-temperature operation because of the absence of permanent magnet. One significant problem in SRM is the high acoustic noise and vibration. The vibration in SRM is caused by the radial forces acting at the stator teeth. Because of the saliency pole configuration in SRM, vibration is prominent. Many studies tried to reduce acoustic noise and vibration in SRM. In this paper, several controls for acoustic noise and vibration reduction are shown. The acoustic noise and vibration reduction from the experiment are also compared in each method.